Assessment of Role of Parental Role in Curbing Empty Calories Consumption in Primary School Children in Gwadabawa - Sarkingobir, Yusuf; Tukur, Ummu; Waheed, Syed Abdul (Jurnal Riset Madrasah Ibtidaiyah, 2025)
Nowadays, the consumption of empty calories is predominating in various societies, including among the children. This is sad, because it is link to adversaries such as hypertension, cancer, diabetes, etc. Thus, this study examined the role of parents in curbing empty calorie consumption among primary school children using a survey method among 160 respondents (key informants). A questionnaire was utilized in conducting the survey research and the findings revealed that parents play a significant cognitive and behavioral role in promoting healthy eating habits among children. Cognitive roles included providing basic nutrition education (63.8%), helping children understand food labeling (21.3%), and meal planning (15.0%). Behavioral roles included demonstrating healthy eating (23.8%), providing healthy food options (38.1%), and monitoring food intake (19.4%). However, factors such as poor nutritional awareness (35.0%), poverty (41.9%), and work-life balance (23.1%) hindered parental involvement. Initiatives to improve parental involvement included creating nutritional awareness (49.4%), legislation (20.0%), job creation (13.1%), and counseling on work-life balance (17.5%). The study highlights the importance of parental involvement in promoting healthy eating habits among children.